PERMEABILITY ANISOTROPY DISTRIBUTIONS IN AN UPPER JURASSIC CARBONATE RESERVOIR, EASTERN SAUDI ARABIA - Sahin, A. (2020)
Most classical reservoir engineering concepts are based on homogeneous reservoirs despite the fact that homogeneous reservoirs are the exception rather than the rule. This is especially true of carbonate reservoirs in the Middle East which are known to be highly heterogeneous. The realistic petrophysical characterization of these kinds of reservoirs is not an easy task and must include the study of directional variations of permeability. Such variation can be incorporated into engineering calculations as the square root of the ratio of horizontal to vertical permeability, a parameter known as the anisotropy ratio. This paper addresses the distribution of anisotropy ratio values in an Upper Jurassic carbonate reservoir in the Eastern Province of Saudi Arabia. Based on whole core data from a number of vertical wells, statistical distributions of horizontal and vertical permeability measurements as well as anisotropy ratios were determined. The distributions of both permeability measurements and anisotropy ratios have similar patterns characterized by considerable positive skewness. The coefficients of variation for these distributions are relatively high, indicating their very heterogeneous nature. Comparison of plots of anisotropy ratios against depth for the wells and the corresponding core permeability values indicate that reservoir intervals with lower vertical permeability yield consistently higher ratios with considerable fluctuations. These intervals are represented by lower porosity mud-rich and/or mud-rich/granular facies. Granular facies, on the other hand, yielded considerably lower ratios without significant fluctuations.